PROFESSIONAL COMPETENCY OF STUDENTS IN DISPLAY DESIGN MAJOR OF COLLEGES AND UNIVERSITIES UNDER GUANGDONG PROVINCE - Chen Yanyan; Chaisirithanya, Kamolmal; Chinatangkul, Chuanchom (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were: (1) to explore the components of professional competency of students in display design major of colleges and universities under Guangdong Province; and (2) to propose the managerial guidelines for professional competency of students in display design major of colleges and universities under Guangdong Province. The research methodology was mixed methodology, including qualitative research and quantitative research. The population includes managers and lecturers of display design majors in universities affiliated to Guangdong Province, total 1896. The adequate sample size were determined by the table (1970) of Krejcie and Morgan, totaling 337. The key informants were as follows: four entrepreneurs were managers with more than eight years of relevant work experience related to the display design industry, including company founders, general managers, executives and senior managers of design companies; four lecturers were teaching display design for more than five years and have trained more than two graduating students in the profession; four students were required to be within three years of graduation and working in a job related to the display design major, obtained by purposive sampling method. The instruments used for data collection were semi-structured interview form, five-point rating scale questionnaire, and Focus Group Discussion form. The statistics used for data analysis were descriptive statistics and Exploratory Factor Analysis as well as content analysis was employed. The research findings revealed that: (1)there were five components on Professional Competency which consisted of Aesthetic, creative and decision-making skills, software operation and construction knowledge, operational and practical skills, art and design basics, corporate training skills; and (2) there were total 19 managerial guidelines on Professional Competency in colleges and universities under Guangdong Province which consisted of four managerial guidelines for component of aesthetic, creative and decision-making skills, five managerial guidelines for software operation and construction knowledge, three managerial guidelines for operational and practical skills, three managerial guidelines for art and design basics, and four managerial guidelines for corporate training skills.